2015
DOI: 10.1111/imm.12528
|View full text |Cite
|
Sign up to set email alerts
|

Thymic stromal lymphopoietin‐induced interleukin‐17A is involved in the development of IgE‐mediated atopic dermatitis‐like skin lesions in mice

Abstract: SummaryAtopic dermatitis (AD) is a chronic inflammatory skin disease associated with elevated levels of allergen-specific IgE. Although thymic stromal lymphopoietin (TSLP) and interleukin-17A (IL-17A) have been considered as important factors in allergic diseases, their relationships in AD have not been fully defined. Here, we show the contribution of TSLP-induced IL-17A responses to IgE-mediated AD-like skin lesions. BALB/c mice passively sensitized by intraperitoneal injections of ovalbumin (OVA)-specific Ig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 66 publications
0
28
0
Order By: Relevance
“…Th1, Th2, Th17 and Th22). The pathogenesis of acute AD is related to Th2‐dominant inflammation, characterized by the dermal infiltration of Th cells, macrophages and eosinophils, increase in allergen‐specific IgE, mast cell activation and Th2 cytokine production (Mizutani et al ., ). Th2 cells secrete the cytokines IL‐4 and IL‐5, that up‐regulate antibody formation via B cells, eosinophils, mast cells and other pathways (Kidd, ).…”
Section: Introductionmentioning
confidence: 97%
“…Th1, Th2, Th17 and Th22). The pathogenesis of acute AD is related to Th2‐dominant inflammation, characterized by the dermal infiltration of Th cells, macrophages and eosinophils, increase in allergen‐specific IgE, mast cell activation and Th2 cytokine production (Mizutani et al ., ). Th2 cells secrete the cytokines IL‐4 and IL‐5, that up‐regulate antibody formation via B cells, eosinophils, mast cells and other pathways (Kidd, ).…”
Section: Introductionmentioning
confidence: 97%
“…Besides, we evaluated the skin mRNA expression of thymic stromal lymphopoietin (TSLP), a cytokine produced by epithelial cells at barrier surfaces, which is believed to be involved in the development of AD . We found that TSLP production was significantly elevated in TLR4 −/− mice compared with that in WT mice upon DNCB administration (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…A lot of studies reveal that imbalance in T helper 1/T helper 2 (Th1/Th2) and defective skin barrier contribute to the pathological mechanism . In AD skin biopsies, the high expression of Th2 cytokines (eg IL‐4, IL‐5 and IL‐13), which in conjunction with other inflammatory mediators, leads to the activation of eosinophils and mast cells, as well as B‐cell switching to pathogenic IgE . Besides, there are two main types of immature skin dendritic cells (DCs): Langerhans cells (LCs) in the epidermis and interstitial (dermal) DCs in the dermis .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that anti‐TSLP antibody inhibited the development of oesophageal eosinophilia and food impaction in a murine model of eosinophilic oesophagitis . In a murine model of AD, treatment with anti‐TSLP antibody inhibited IgE‐mediated AD‐like skin lesions and IL‐17A production in the lymph nodes . In a chronic HDM‐induced asthma model, an anti‐TSLP antibody reversed airway inflammation, prevented structural alterations, and decreased airway hyper‐responsiveness to methacholine and TGF‐beta1 level .…”
Section: Keratinocyte‐derived Chemokines and Cytokines That Are Direcmentioning
confidence: 99%